2009
DOI: 10.1111/j.1541-0072.2009.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Co‐Governance: Examining the “Chemistry” of Home‐Care Networks in Germany, England, and Quebec

Abstract: This article aims at studying the dynamics of organized home care and particular problems in the delivery of social services, analyzed against the background of the international recasting of welfare systems. Challenging an influential academic discourse on the advent of new forms of network governance thought to improve service provision, three jurisdictions-Germany, England, and Quebec-are compared with regard to how home-care networks are actually configured and the rationales which appear to shape the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Lowndes and Skelcher [13], for instance, found in a study of UK urban regeneration partnerships that the three governance mechanisms (contracts, hierarchy, and relational) can exist in network forms of inter-organizational collaboration, and that these modes can co-exist and depend largely on the stage in the life-cycle of the network organization. Bode and Firbank [31] studied home-care networks for the elderly in various countries and found that such networks can have very different governance mechanisms, ranging from more bureaucratic to more market-oriented. Berbée et al [33] distinguish between contractual and relational governance mechanisms in health care exchange relationships and found in a Belgian health care institute that contractual and relational governance reinforce each other rather than be conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowndes and Skelcher [13], for instance, found in a study of UK urban regeneration partnerships that the three governance mechanisms (contracts, hierarchy, and relational) can exist in network forms of inter-organizational collaboration, and that these modes can co-exist and depend largely on the stage in the life-cycle of the network organization. Bode and Firbank [31] studied home-care networks for the elderly in various countries and found that such networks can have very different governance mechanisms, ranging from more bureaucratic to more market-oriented. Berbée et al [33] distinguish between contractual and relational governance mechanisms in health care exchange relationships and found in a Belgian health care institute that contractual and relational governance reinforce each other rather than be conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Governance mechanisms in health care networks are, therefore, based on hierarchical, contractual, or relational governance, or a combination of these three. Although relational governance is traditionally thought to be the primary governance mechanism in networks [20,29], the literature suggests that this might not always be the case, at least not in health care organizations [31]. …”
Section: Methodsmentioning
confidence: 99%
“…But market pressures and the overall weakening of consensus building set clear limits to ‘democratic’ governance in its own ways as evidenced in home care for elderly for example (Bode 2006). Home care clearly operates through arrangements embracing conflicting rationales (Bode and Oscar 2009). Yet often, making money by capturing customers easily overrules the building of trust‐based relationships with users and public bodies (Bode 2007).…”
Section: Users As Consumers Of Health and Old Age Care Services?mentioning
confidence: 99%
“…In this case co‐production might be closer to citizenship. Yet given the lessening of political influence by organizations grounded in their local communities (Bode 2006, 2007; Bode and Oscar 2009), it is hard to imagine that clients or their relatives are empowered truly to participate in the co‐production of care services. Finally, if pressures to promote independence are enforced because of potential cost saving, as may be the case for direct payments (Fyson 2009), this might lead to inequality of outcomes for service users and increase their vulnerability to abuse.…”
Section: Users As Consumers Of Health and Old Age Care Services?mentioning
confidence: 99%
See 1 more Smart Citation